(untitled) (Construction Economics and Building, 2015)
Building Information Modelling (BIM) is seen as a panacea to many of the ills confronting the Architectural, Engineering and Construction (AEC) sector. In spite of its well documented benefits the widespread integration of BIM into the project lifecycle is yet to occur. One commonly identified barrier to BIM adoption is the perceived legal risks associated with its integration, coupled with the need for implementation in a collaborative environment. Many existing standardised contracts used in the Australian AEC industry were drafted before the emergence of BIM. As BIM continues to become ingrained in the delivery process the shortcomings of these existing contracts have become apparent. This paper reports on a study that reviewed and consolidated the contractual and legal concerns associated with BIM implementation. The findings of the review were used to conduct a qualitative content analysis of the GC21 2nd edition, an Australian standardised construction contract, to identify possible changes to facilitate the implementation of BIM in a collaborative environment. The findings identified a number of changes including the need to adopt a collaborative contract structure with equitable risk and reward mechanisms, recognition of the model as a contract document and the need for standardisation of communication/information exchange.